2017
DOI: 10.14807/ijmp.v8i2.576
|View full text |Cite
|
Sign up to set email alerts
|

Application of queuing theory to a fast food outfit: a study of blue meadows restaurant

Abstract: The study evaluated the queuing system in Blue Meadows restaurant with a view to determining its operating characteristics and to improve customers' satisfaction during waiting time using the lens of queuing theory. Data was obtained from a fast food restaurant in the University of Benin. The data collected was tested to show if it follows a Poisson and exponential distribution of arrival and service rate using chi square goodness of fit. A 95% confidence interval level was used to show the range of customers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Queuing theory has been used in many applications, financial institution [7,8,3], transportation [4,9], health care delivery [10,11], day to day life [12], educational sector [13,14], Restaurant [15,16], Super market [17,18] among others.…”
Section: Fig 1 a View Of Basic Queuing Processmentioning
confidence: 99%
“…Queuing theory has been used in many applications, financial institution [7,8,3], transportation [4,9], health care delivery [10,11], day to day life [12], educational sector [13,14], Restaurant [15,16], Super market [17,18] among others.…”
Section: Fig 1 a View Of Basic Queuing Processmentioning
confidence: 99%
“…(Koh et al, 2014b) Queueing management has been used quite successfully in a number of service-oriented businesses to reduce cycle time in a busy system, such as hospitals and restaurants, as well as to boost throughput and efficiency, many academics have previously used queuing theory to simulate the fast food operation and numerous service industries. (Gumus et al, 2017b) There are a lot of different reasons as to why there are queues in fast food restaurants. One of them is very common but important reason being a significant chunk of customers (i.e., about 65% of family groupings) will first reserve a table by leaving one of the members of the party there or (less frequently) by putting their stuff there to avoid losing out on a place to sit after waiting in long queues.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Blue Meadow's Queuing Model, backed by tests for Poisson distribution and Chi-Square Goodness of Fit for the peak period, off period, decision rule, and exponential distribution, as well as FIFO, Single Channel, Multiple Channels, are some of the well-known models used over the years in the fast-food industries. (Gumus et al, 2017a) Queuing theory is a subfield of mathematics that investigates the formation, operation, and causes of queues. (Basir & Chandrashekar, 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…Sallam and Zobu [22] using simulation data on a queuing model with sequential two stations (stages) and all other conditions well defined, concluded that the simulation results approximated the theoretical results. So many authors have used queuing models in one way or the other among whom are Qureshi et al [21], Srinivas et al [25], Famule [8], Keaogile et al [13] ,Gumus et al [10], Kembe et al [14], Aradhye and Kallurkar [4], Cho et al [6] , Maedeh et al [15], Adan [1], Conte et al [7], Ugwuishiwu et al [27] ,Afrane and Appah [2] , Kama and Mankilik [12], Mukherjee and Whalen [16], Jo et al [11].…”
Section: Literaturementioning
confidence: 99%